States Of Exception : Everyday Life and Postcolonial Identity - Ganguly, Keya (Book collections on Project MUSE., 2001)
A philosophical anthropology of everyday experience, this book is also a deeply informed and thought-provoking reflection on the work of cultural critique. States of Exception looks into a community of immigrants from India living in southern New Jersey--a group to whom the author, as a daughter of two of its members, enjoyed unprecedented access.